The correlation between the frequency of food consumption containing gluten and casein toward caries in children with autism spectrum disorders - Tiffany M Indrawati; Agus Susanto; Inne S Sasmita (Faculty of Dentistry, Universitas Trisakti, 2023)
Background: Foods containing gluten and casein are widely consumed by children with autism spectrum disorder (ASD). Indeed, they are among their favorite foods. These foods contain carbohydrates, the primary substrate causing caries. Dental caries is one of the oral manifestations in children with ASD due to an imbalance in the demineralization and remineralization of tooth enamel. This study aimed to determine the relationship between food containing gluten and casein and the incidence of dental caries in children with ASD at the Biruku Indonesia Foundation (Bandung City, Java, Indonesia). Methods: This quantitative study used an analytical observational design with a cross-sectional approach. The research sample consisted of 17 subjects selected using the total sampling technique. Data were obtained after the Food Frequency Questionnaire (FFQ) and intraoral examination (DMFT/dmft score) were completed by the children’s parents. Correlation analysis was performed using Spearman’s rank test. Results: A total of 11 children, 64.7% had a low frequency of consuming food containing gluten and casein, whereas 6 children (35.3%) had a high frequency with a high dmft index (6.2) and a low DMFT index (1.5). Correlation analysis showed a negative correlation or inverse relationship between the two variables. Moreover, a significant relationship was found between consuming food containing gluten and casein and the dmft score (P value = 0.0498) and DMFT score (P value = 0.0383). Conclusion: Consuming food containing gluten and casein has a negative correlation or inverse relationship with dental caries in ASD children.